2018
DOI: 10.1037/ort0000327
|View full text |Cite
|
Sign up to set email alerts
|

The impact of familial expressed emotion on clinical and personal recovery among patients with psychiatric disorders: The mediating roles of self-stigma content and process.

Abstract: The present study examined the associations of familial expressed emotion (EE) with clinical and personal recovery among patients with psychiatric disorders, as well as the potential mechanisms underlying these associations. Guided by the content-process theory of self-stigma, we hypothesized that EE would be negatively associated with clinical and personal recovery and that these associations would be mediated by self-stigma content and process. A total of 311 patients with psychiatric disorders completed que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 79 publications
7
12
0
Order By: Relevance
“…The results of our study indicated that family criticalness was directly related to personal recovery. This result is consistent with the findings of a previous study (Chan & Lam, 2018). Our findings also showed that family criticalness was indirectly related to personal recovery through the effect of self-esteem.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The results of our study indicated that family criticalness was directly related to personal recovery. This result is consistent with the findings of a previous study (Chan & Lam, 2018). Our findings also showed that family criticalness was indirectly related to personal recovery through the effect of self-esteem.…”
Section: Discussionsupporting
confidence: 94%
“…Built upon prior research findings that family network size, perceived family support, family criticalness were identified to be related to personal recovery among individuals with mental illness (Biegel et al, 2013;Chan & Lam, 2018;Pernice-Duca, 2010), this study aims to examine the indirect effects of self-esteem and selfefficacy in the relationship between these three family network variables and personal recovery in Chinese people with mental illness in Hong Kong, a Chinese society which is still greatly influenced by Confucian values (Chen et al, 2019). We proposed the following hypotheses: Hypothesis 1: A large family network is associated with a high level of recovery directly and indirectly through the effects of high self-esteem and high self-efficacy.…”
Section: The Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Negative social interactions refer to "unpleasant social encounters and interactions that are characterized by conflict, excessive demands, and/or criticism" [12]. Negative social interactions can exacerbate symptoms and impede recovery from mental illness [13]. Studies have found that negative social interactions are also related to poor quality of life [9,14].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the role of the family in the prevention, treatment, and rehabilitation of patients with mental disorders, participation of the family is considered as the main principle in the treatment program of patients with mental disorders [20,21]. According to the essential role of family caregivers, their negative attitudes may hinder the procedure of treatment and recovery of patients with mental disorders, whereas the positive attitude may fulfill the patients' needs.…”
Section: Introductionmentioning
confidence: 99%